STRUCTURE AND STRENGTH OF MAGNESIA CEMENT FROM DOLOMITE - Ayimbetov, M.; Yo‘ldosheva, G.Z. (SCIENCE and SOCIETY, 2026)
The article is assigued to the study of magnesium Portland cement (MPC) produced from dolomite of Karakalpakstan. The chemical composition of the raw material was analyzed, while the microstructure of the cement stone and hydration dynamics were examined. Data on compressive strength and porosity of the samples are provided; the advantages of using MPC in aggressive environments and prospects for implementing this technology at the regional level are discussed.